Framing the West : race, gender, and the photographic frontier in the Pacific Northwest - Williams, Carol, 1956- (Oxford University Press, 2003)
This work argues that photography was intrinsic to British territorial expansion and settlement on the Northwest coast of America. Williams shows how male and female settlers used photography to establish control over the territory and its indigenous inhabitants, as well as how native peoples eventually turned the technology to their own purposes. Photographs of the region were used to stimulate British immigration and entrepreneuralism, and images of babies and children were designed to advertise the population growth of the settlers. Although photographs of Indians were taken by Anglos to document their "disappearing" traditions and to show the success of missionary activities, many Indians proved receptive to photography and turned posing for the white man's camera to their own advantage. This book will appeal to those interested in the history of the West, imperialism, gender, photography, and First Nations/Native America.